KONTRIBUSI DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP ADEKUASI PENYESUAIAN DIRI DI SEKOLAH PADA SISWA SMP - Novitasari, Dyah Ayu; Soeharto, Soeharto; Hidayat, Sri Wiyanti (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2014)
This research was surveys research. The participant were eighth grade Junior High School, which consisted of 105 students. The technique of collecting data that was used was questionnaire about students? self-adjustment adequacy and peer?social support. The technique of analyzing the data used for the first and second hypothesis was t-test one side (One Tail Test) with left tail test. Furthermore, simple regression linear technique with SPSS 16 was used to analyze the third hypothesis. The results indicate of this study that: (1) the students? self adjustment adequacy  belong  to  the  medium category, the results of the calculation indicate t count> t table is 4.379> 1.98. (2) the peers? social support those a belong to the high category, the result of the calculation indicate tcount <t table is 0.473 <1.98. (3) contribution of peers? social support to the students? self adjustment adequacy is 35,4 %, obtained from the results of the calculation of R square of 0,354.